The Quality of the Rona Senandhika Kebaya with the Application of Floral Beading Details on Chantilly Lace - Tsabita Luthfia Anjani; Nazwa Salsabila; Noviana Safitri; Istifarini Dzikri Nurfika Aguslia; Wulansari Prasetyaningtyas; Yunius Mujianto (Universitas Negeri Semarang, 2026)
This Study aimed to create the Rona Senandhika kebaya by applying floral beading details to Chantilly lace material and to determine the feasibility level of the resulting product. The study employed a practice-based research approach, which positions the creative practice as an integral part of the research process. The research stages included concept development, design planning, pattern making, fabric cutting, sewing, the application of floral beading details, and the final finishing process. Product feasibility testing was conducted using an assessment sheet involving 21 panelists, consisting of 3 expert panelists and 18 students of Fashion Education who had completed the Haute Couture and Women's Garment Production courses. The data were analyzed using descriptive percentage analysis. The results showed that the Rona Senandhika kebaya was successfully created in accordance with the designed concept through the combination of Chantilly lace material and floral beading details, resulting in a feminine, graceful, and elegant appearance. The feasibility test results indicated that the design aspect achieved a score of 94.7%, the size aspect 96.7%, the aesthetic aspect 96.7%, the sewing technique aspect 96.5%, and the uniqueness aspect 94.6%. All aspects were categorized as Highly Feasible. Therefore, the application of floral beading details to Chantilly lace material was considered effective in enhancing the aesthetic value and producing a kebaya that is feasible and possesses a strong design character. Keywords: kebaya, floral beading, Chantilly lace, feasibility assessment, fashion design.